THE INFLUENCE OF L1/L2 BASED STRATEGIES TOWARD STUDENTS’ SPEAKING ABILITY IN IKIP BUDI UTOMO MALANG - PUSPITASARI, IKE DIAN; Lestari, Hernina Dewi (Universitas Negeri Semarang, 2018)
In speaking English, students should concern with vocabulary items, grammar, intonation, body language and so on. This research purposes to know the ability of students taught by using L1/L2 based strategies and students taught without L1/L2 based strategies, and also to know the influence of L1/L2 based strategies toward students’ speaking ability. The research method was quasi-experimental which used two groups as Experimental Group (EG) and Control Group (CG). The research subjects were 90 students. The EG showed that there was difference before and after treatment although it was not significant. It also occurred for CG. However, by comparing the scores of both groups, this research found that sig. value is 0.000, in which the probability value (pvalue) significant level (α=0.05). Hence, it is strengthen by tvalue 3.807 with df 44 (n-1) compared to ttable (2.015). Thus, it can be concluded that Ho is rejected. There is positive influence of L1/L2 based strategy towards speaking ability of students in IKIP Budi Utomo Malang.